On the issue of using expenditure functions in simulation of pneumatic links of the "throttle - capacity" type - Leontiev, Dmytro; Savchenko, Yevhen; Harmash, Anton; Suhomlyn, Oleksandr; Sinelnik, Danylo; Леонтьєв, Дмитро Миколайович; Савченко, Євген Лукич; Гармаш, Антон Андрійович; Сухомлин, Олександр Вячеславович; Cінельнік, Данило Богданович (Харківський національний автомобільно-дорожній університет, 2022)
Problem. When studying the work processes that occur in pneumatic or electropneumatic circuit of brake systems or pneumatic suspension systems of a wheeled vehicle, researchers use various expenditure functions on the basis of which they draw scientific conclusions and obtain scientific results, while they do not think about the fact that the functions are credible or not. The choice of the expenditure function, for researchers, is an actual scientific task, which should have a scientific justification and should not have a formalized nature. Goal. The aim of the study is to compare the expenditure functions to determine the nature of their influence on the dynamic processes that occur during filling or emptying links of the pneumatic circuit. Methodology. The approaches adopted in the work to solving the set goal are based on the analysis of the results of simulation modeling of work processes in pneumatic circuit. Results. A comparison of the research results obtained in this work with each other and with the results obtained in experimental studies, allowed us to establish the peculiarities of the course of work processes in the pneumatic circuit links when using different expenditure functions. It was established that, depending on the choice of the expenditure function, with the same initial conditions of simulation modeling, the results of the study can differ by up to 40%. Originality. The use of a universal basis of simulation modeling, based on various expenditure functions, enabled to establish that it is possible to propose new functions that better describe the working process in a pneumatic circuit than the known ones. Practical value. The obtained results can be recommended in the practice of simulation modeling of work processes in pneumatic or electropneumatic circuits of brake systems and systems of pneumatic suspension of wheeled vehicles.
Щодо питання використання витратних функцій при моделюванні пневматичних ланок типу «дросель – ємкість»
Keywords: expenditure function; flow function; pneumatic circuit; brake system; pneumatic suspension system; витратна функція; функція витрати; пневматичний привід; гальмова система; система пневматичного підресорювання; 629.021; 10.30977/AT.2219-8342.2022.51.0.05